Modification of Materials and Thickness Layer of Radial Piercing Beamport (RPB) Reflector on Kartini Reactor for Boron Neutron Capture Therapy (BNCT) - Octaviana Erawati F; Riyatun R; Suharyana S (Department of Physics, Sebelas Maret University, 2015)
Modification of materials and thicknesses reflector RPB of Kartini reactor has been done to support cancer therapy with BNCT method. Modifications have been investigated by computer simulation method based on software MCNP5. Neutron beam for BNCT must be fulfill the criteria recommended by International Atomic Energy Agency (IAEA), two of which are n.cm-2.s-1 and . Before the modification of the neutron beam done, the measurements in the end of the RPB indicate that n.cm-2.s-1 and . These conditions were not fulfilling the requirements of the IAEA, so that the modification of the reflector material and thickness layer of RPB should be done. Those modifications were done by varying the materials PbF2, Pb-nat, 209Bi, Ni-nat (95%) and Fe-nat. The simulation result showed if the material Ni-nat (95%) on the thickness 1.5 cm was use as a coating material reflector optimally. The results after the modification showed that increased 7,54% with the increase amounted to n.cm-2.s-1. decrease 21,45%, then decreasing the value of became 1,70. After the modification the results has not yet fulfill the criteria of the IAEA. Because of the reflector was not the only guide neutron beam. Moderator and filter have not been optimized to deliver results for files that match the criteria of the IAEA for BNCT. Therefore, in future studies modified with the addition of a neutron moderator and also filter is expected to help increasing the quantity of and decreasing of .